Lazer virtual e a pessoa idosa na pandemia da COVID-19 no contexto da atenção primária à saúde: criatividades interventivas/ Virtual leisure and the elderly in the COVID-19 pandemic in the context of primary health care: interventional creativity/ Entretenimiento virtual y personas mayores en la pandemia COVID-19 en el contexto de la atención primaria de salud: creatividades intervencionistas - da Silva Santos, Álvaro (Journal Health NPEPS, 2021)
EDITORIAL